A Highly Conductive All‐Carbon Linked 3D Covalent Organic Framework Film. Issue 40 (8th September 2021) - Yang, Yizhou; Mallick, Suman; Izquierdo‐Ruiz, Fernando; Schäfer, Clara; Xing, Xing; Rahm, Martin; Börjesson, Karl
Abstract: Here an all‐carbon linked 3D covalent organic framework (COF) is introduced by employing a templated surface reaction in a continuous flow (TSRCF). The presented method of synthesis provides spatial control over the reaction chemistry and allows for the creation of ultrasmooth COF films of desired thickness and significant crystallinity. The films show high electrical conductivity (≈3.4 S m −1 ) after being doped with tetracyanoquinodimethane (TCNQ), setting a new record for 3D COF materials. The concurrence of 3D nanosized channels and high conductivity opens up for a number of hitherto unexplored applications for this class of materials, such as high surface area electrodes, electrochemical transistors, and for electronic sensing. Abstract : The preparation of all‐carbon linked 3D covalent organic frameworks of high quality is challenging. It is reported here a bottom‐up method, which successfully realize the fabrication of such a material in the form of a continuous and smooth film on different substrates. The films show a record high electrical conductivity within the 3D covalent organic framework (COF) family.